Citrus Diseases Exotic to Florida: Witches' Broom Disease of Lime (WBDL) - Kuang Ren Chung; I. A. Khan; Ronald H. Brlansky (EDIS)
This paper discusses Witches' Broom Disease of Lime (WBDL). This document is Fact Sheet PP-228, one of a series of the Plant Pathology Department, UF/IFAS Extension. Original publication date: April 2006.